An Appropriate Use of IMap Produces Correct Statistical Results: A Reply to McManus (2013) "IMap and IMap2 Produce Erroneous Statistical Maps of Eye-Movement Differences". (May 2014) - Miellet, Sébastien; Lao, Junpeng; Caldara, Roberto
McManus (2013, Perception, 42, 1075–1084) contends the validity of the statistical approach adopted in previous versions of i Map (namely, i Map and i Map2; Caldara & Miellet, 2011, Behavior Research Methods, 43, 864–878), casts doubts on earlier results obtained with the toolbox, and offers an altered version of the code. Here we dispute these claims and argue that while some of the arguments put forward are valid, McManus's conclusions are misleading, since they are based on a partial use of the toolbox. Moreover, we compared i Map with the alternative code offered by McManus and objectively demonstrate that McManus's approach is underpowered and flawed. i Map offers an appropriate and effective alternative to the commonly used regions of interest approach for statistical analyses of eye-movement data.